Critical Role of Removing Impurities in Nickel Oxide on High‐Efficiency and Long‐Term Stability of Inverted Perovskite Solar Cells. Issue 18 (4th March 2022) - Wang, Shuangjie; Li, Yuke; Yang, Jiabao; Wang, Tong; Yang, Bowen; Cao, Qi; Pu, Xingyu; Etgar, Lioz; Han, Jian; Zhao, Junsong; Li, Xuanhua; Hagfeldt, Anders
Abstract: The performance enhancement of inverted perovskite solar cells applying nickel oxide (NiO x ) as the hole transport layer (HTL) has been limited by impurity ions (such as nitrate ions). Herein, we have proposed a strategy to obtain high‐quality NiO x nanoparticles via an ionic liquid‐assisted synthesis method (NiO x ‐IL). Experimental and theoretical results illustrate that the cation of the ionic liquid can inhibit the adsorption of impurity ions on nickel hydroxide through a strong hydrogen bond and low adsorption energy, thereby obtaining NiO x ‐IL HTL with high conductivity and strong hole‐extraction ability. Importantly, the removal of impurity ions can effectively suppress the redox reaction between the NiO x film and the perovskite film, thus slowing down the deterioration of device performance. Consequently, the modified inverted device shows a striking efficiency exceeding 22.62 %, and superior stability maintaining 92 % efficiency at a maximum power point tracking under one sun illumination for 1000 h. Abstract : High‐quality NiO x nanoparticles have been synthesized via an ionic liquid‐assisted synthesis method (NiO x ‐IL). The inverted perovskite solar cell based on a NiO x ‐IL hole transport layer exhibits a striking efficiency exceeding 22.62 %, and a superior operational stability maintaining 92 % of its initial efficiency at a maximum power point tracking under one sun illumination for 1000 h.